A generalized ICA algorithm - Stoll, B.; Moreau, E. (IEEE signal processing letters, 2000)
In this paper, we consider the source separation problem through a block algorithm based on the maximization of contrast functions. We propose a new contrast with parameterized cross-cumulants. It allows us to put three classical contrasts in a common framework. Following the same spirit of the independent component analysis (ICA) algorithm, we derive the analytical solution for the case of two sources. Finally, a computer simulation is performed to illustrate the behavior of a Jacobi-like algorithm for the maximization of the new contrast.